ACCESS-AM2 Southern Ocean cloud and radiation data for k-means clustering and analysis - Sonya L. Fiddes (Zenodo, 2022)
The ACCESS-AM2(Australian Community Climate and Earth-System Simulator - Atmospheric Model Version 2) data and k-means analysis used for thestudy described in Fiddes et al. 2022 ' Southern Ocean cloud and shortwave radiation biases in a nudged climate model simulation: does the model ever get it right?' . Included files: modis_cluster_centres_2015-2019.nc - kmeans derived cluster centres for MODIS modis_cluster_labels_2015-2019.nc - kmeans derived cluster labels for MODIS bx400_cluster_labels_2015-2019.nc - kmeans fitted cluster label for model COSP_vars_bx400_2015-2019.nc - model data for analysis The code that performs the analysis/generates this data and has instructions for where to download MODIS datacan be found here:https://github.com/sfiddes/code_for_publications_2022/tree/main/ACCESS_cloud_radiation_eval This project was funded by the Australian Government as part of the Antarctic Science Collaboration Initiative program, under the Australian Antarctic Program Partnership, ASCI000002.